Jejunal Absorption and Secretion of Calcium in Patients with Chronic Renal Disease on Hemodialysis - Parker, Tom F. (1974)
10 patients with chronic renal disease on hemodialysis and 8 normals were studied by constant jejunal perfusion of calcium gluconate solutions, using polyethylene glycol as a nonabsorbable marker. Results in normals indicated that calcium absorption from 1 and 5 mM calcium solutions is mainly active. Absorption from 5, 15, and 20 mM solutions was a linear function of luminal calcium concentration, suggesting that the active transport carrier is saturated when luminal calcium concentration is greater than 5 mM and indicating that the increment in absorption at higher luminal concentrations is mainly the result of passive absorption. With 1 mM calcium, normals absorbed calcium against a concentration gradient, whereas the patients secreted calcium. Absorption in the patients was much less than normal with 5, 15, and 20 mM luminal calcium concentrations; however, the slope of this linear (passive) portion of the curve was normal. Unidirectional calcium fluxes were measured with calcium-47. Flux out of the lumen was depressed 2.5-fold in the patients, but flux into the lumen was normal. Xylose, urea, and tritiated water were absorbed normally, indicating no generalized abnormality of jejunal transport in these patients. Endogenous calcium secretion, estimated by the amount of calcium added to a calcium-free solution, was normal in the dialysis patients. These results indicate that active calcium absorption is markedly depressed in patients with chronic renal disease who are receiving hemodialysis therapy. On the other hand, passive calcium movement and endogenous calcium secretions are normal.